2015
DOI: 10.1159/000439024
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Postnatal Renal Function in Twin Anemia-Polycythemia Sequence

Abstract: Objective: To evaluate the short-term renal function in neonates with twin anemia-polycythemia sequence (TAPS). Methods: All consecutive monochorionic twins with TAPS with double survivors admitted to three European centers were included in this retrospective study. Each twin pair was matched for gestational age at birth with a control twin pair unaffected by TAPS or twin-twin transfusion syndrome. Creatinine and urea levels in the first week after birth were recorded. Short-term postnatal renal dysfunction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…In addition to lower Hb levels, donor twins with TAPS also have significantly lower albumin and total protein levels compared to recipient twins, suggesting that the inter-twin transfusion process does not only concern red blood cells but also proteins and albumin (Verbeek et al, 2013). Chronic inter-twin transfusion in TAPS may also cause short-term renal dysfunction: Verbeek et al (2015) found that donor twins with TAPS have higher creatinine levels than recipients, probably due to chronic renal hypoperfusion. Whether donor twins may also have permanent renal damage and long-term renal complications is not known.…”
Section: Short-term Neonatal Outcomementioning
confidence: 99%
“…In addition to lower Hb levels, donor twins with TAPS also have significantly lower albumin and total protein levels compared to recipient twins, suggesting that the inter-twin transfusion process does not only concern red blood cells but also proteins and albumin (Verbeek et al, 2013). Chronic inter-twin transfusion in TAPS may also cause short-term renal dysfunction: Verbeek et al (2015) found that donor twins with TAPS have higher creatinine levels than recipients, probably due to chronic renal hypoperfusion. Whether donor twins may also have permanent renal damage and long-term renal complications is not known.…”
Section: Short-term Neonatal Outcomementioning
confidence: 99%
“…6 TAPS is considered a form of TTTS, and a recent study showed that the donor of TAPS has higher creatinine levels than the recipient because of chronic intertwin transfusion. 7 In preterm infants, the symptoms of HHS are vague and nonspecific, which makes it difficult to detect the problem. 2 In our case, the patient also showed sepsis-like clinical presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Anämische Donor-Zwillinge haben neben dem niedrigen Hämoglobinwert auch signifikant erniedrigte Werte an Albumin und Gesamtprotein [24]. Verbeek und Mitarbeiter fanden weiterhin heraus, dass die Nierenfunktion postnatal eingeschränkt sein kann [25]. Ob diese Funktionseinschränkung persistiert, ist noch unklar.…”
Section: Schwangerschaftsausgang Bei Tapsunclassified